Spiritual Assessment Based on Matthew 22:37-40: Faith Integration, Communal Spirituality, and Environmental Stewardship in Indonesian Christian Higher Education - I Made Suardana; Ezra Tari; Oscard Lumban Tobing; Yasinta Waang; Abdiel Enrique Sánchez Revilla (Sakura Digital Nusantara, 2026)
This study addresses the need for a contextual spiritual assessment model in Christian higher education in East Nusa Tenggara, Indonesia, by examining the internalization of the Law of Love (Matthew 22:37–40) in personal spirituality, integration of faith and reason, and environmental stewardship. A descriptive-quantitative survey was conducted with 94 students purposively sampled from four theological institutions in Kupang. Data were analyzed using descriptive statistics, primarily frequency distributions and percentage analysis. The findings revealed that 95.7% of respondents affirmed love as the foundational basis for life decisions (combined